The impact of social support and stress on academic burnout among medical students in online learning: The mediating role of resilience - Liu, Yue; Cao, Zhe (Frontiers in Public Health, 2022)
Background: As the COVID-19 pandemic continues, online learning and long-term isolation from social and clinical settings has exacerbated mental health problems and symptoms of academic burnout among medical students. However, few studies have discussed symptoms of academic burnout as a result of reduced social support, and increased stress among medical students during the process of online learning. To fill this gap, this study investigated the influencing factors and mechanism of academic burnout in medical students' online learning process. Both the positive inhibition effect of positive factors such as social support, and the negative aggravation effect of negative factors such as stress were explored, while the mediating and protecting role of resilience is also discussed. Method: We collected survey data from a total of 817 medical students from a medical school in China who participated in online learning during the fall 2021 semester. An online questionnaire was sent to the students in January, 2022. Items adapted from the DASS Scale developed by Lovibond and Lovibond were used to measure medical students’ stress levels. The perceived social support of medical students was assessed by the Gregory MSPSS. Resilience was evaluated by the 10-Item Connor–Davidson Resilience Scale (CD-RISC). Items from the Maslach Burnout Inventory–Student Survey (MBI-SS) were used to calculate students’ academic burnout. Descriptive analysis, correlation analysis, hierarchical linear regression analysis and structural equation modeling were used to analyze the collected data. Results: The results identified that in the context of online learning there was a positive correlation between medical students’ stress and academic burnout, and their resilience played a partial mediating role. However, social support did not directly affect academic burnout, but inhibited the prevalence of academic burnout through resilience. In addition, stress was negatively related to resilience, while social support was positively related to resilience. Resilience was found to be negatively related to medical students’ academic burnout in online learning. Conclusion: The results of this study can provide a reference for the future development of appropriate educational strategies and coping measures to ameliorate the academic burnout of medical students.